Knowledge of the risk factors of non-communicable diseases (NCDs) among pharmacy students: findings from a Malaysian university - Elnaem, Mohamed Hassan; Jamshed, Shazia Qasim; Elkalmi, Ramadan (Taylor & Francis, 2019)
Non-communicable diseases (NCDs) are a global health burden that affects a broad scope of individuals worldwide. Pharmacists, as members of the multidisciplinary team, play a significant role in promoting public awareness towards potential risk factors for NCDs. This study aims to gauge the knowledge of NCDs risk factors among pharmacy students of a Malaysian public university. This paper also outlines perspectives of pharmacy students on the strategies to raise the awareness of NCDs risk factors. A descriptive cross-sectional study was conducted in the Faculty of Pharmacy, International Islamic University Malaysia. Self-administered questionnaires were pretested and validated before being distributed to pharmacy students across different years of study. The data indicated an average level of knowledge towards risk factors of NCDs among study participants with no significant differences in knowledge between male and female genders (p = 0.583). However, there is a significant difference in knowledge concerning the year of study (p < 0.001); as positive correlation can be seen between the level of education and the knowledge of NCDs risk factor. Most of the students (75%) were unaware of the planning by the Ministry of Health (MOH) to control NCDs. Reinforcement of NCDs-related education activities is imperative in order to increase the overall awareness concerning the risk factors of NCDs among future pharmacy practitioners. Further collaborations between educational institutions and the MOH were proposed to help raise awareness of NCDs risk factors among the younger population.